PENGEMBANGAN RUBRIK HASIL BELAJAR MATEMATIKA UNTUK ASPEK KOGNITIF PADA MATERI BANGUN DATAR - Hanifah Eka Wati (PENDAS MAHAKAM: Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2017)
AbstractMathematics learning should emphasize in-depth understanding of concepts, not just learning by memorization. So it is necessary effort enough to improve learning outcomes, especially learning outcomes on the cognitive aspect. The purpose of this study is to develop and use the rubric of assessment of mathematics learning outcomes for the cognitive aspects of flat wake material using Boom's Taxonomy of Educational Objectives. Learning model used is model of cooperative learning type think pair share and type two stay two stray. Research method by using quasi experiment. Development of rubric of learning result of mathematics on cognitive aspect by applying indicator on Bloom theory that is: Knowledge, Comprehension, Application, Analysis, Synthesis & Evaluation. And there are differences in mathematics learning outcomes between the type of think pair share and the two stay two stray type.Keywords: Learning Outcomes Mathematics, Cognitive Aspects, Bloom's Taxonomy